Gastric cancer: diagnosis and treatment options - Shrestha, MI (Journal of Institute of Medicine Nepal, 2007)
Background: Overall incidence of primary gastric cancer has steadily declined in the western countries, however it is still prevalent in northern and south Asian countries. The exact prevalence in Nepal is still to be known, however according to the hospital based statistics, it seems to be the commonest cancer in Tribhuvan university teaching hospital followed by lung carcinomas. Over all, the incidence of distal stomach tumors has greatly declined, but reported cases of proximal gastric carcinomas, including tumors at the gastroesophageal junction, have increased. Early diagnosis of gastric cancer has been very difficult because most patients are asymptomatic in the early stage. Weight loss and abdominal pain often are late signs of tumor progression. Chronic atrophic gastritis, Helicobacter pylori infection, smoking, heavy alcohol use, and several dietary factors have been incriminated to increase the risks for gastric carcinomas. Esophagogastroduodenoscopy is the preferred diagnostic modality for evaluation of patients in whom stomach cancer is suspected. Accurate staging of gastric wall invasion and lymph node involvement is important for determining prognosis and appropriate treatment. Endoscopic ultrasonography, in combination with computed tomography and operative lymph node dissection, may be involved in staging the tumor. Treatment with surgery alone offers a high rate of failure. Chemotherapy and radiotherapy have not improved survival rates when used as single modalities, but combined therapy has shown some promise. Primary prevention, by control of modifiable risk factors and increased surveillance of persons at increased risk, is important in decreasing morbidity and mortality. The full text of this paper is available at Journal of Institute of Medicine website